Lte security authentication protocol in 3GPP/WLAN internetworking - Vu, Duc Thien (2012)
Serving the high demand of high speed cellular communication, the 3rd Generation Partnership Project (3GPP) is developing System Architecture Evolution (SAE)/Long Term Evolution (LTE) architecture for the next generation mobile communication system. The SAE/LTE architecture provides secured access for mobile user to non-3GPP network such as WLAN. While 3GPP has the advantage of wide area and universal roaming as well as the well developed managing system, WLAN has the advantage of low cost, high bandwidth and data rate. As a result, the interconnection between 3GPP-WLAN networks brings users a combined advantage. In 3GPP-WLAN internetwork, each party of the connection has to have an authentication process to ensure security. To do this task, Extensible Authentication Protocol - Authentication and Key Agreement (EAP-AKA) is used. Based on EAP-AKA, Mr Mun Hye Ran proposed a new protocol that can overcome most of EAP-AKA vulnerabilities. However, the new protocol still has the issue of Message Authentication Code feasibility and Man-in-the middle attack threat. In this project, we analyze the threats and attacks in 3GPP/WLAN internetwork together with the Improved EAP – AKA protocol. Based on this analysis, we suggest some modification for the Improved EAP – AKA protocol to make it feasible and able to prevent Man-in-the-middle attack more effectively. In the end, we create a model in SPIN to simulate the authentication and attack process and verify the protocol.